PREDATORY PRICING: SINGLE- FIRM DOMINANCE, EXCLUSIONARY ABUSE AND PREDATORY PRICES (PART 3) - Jan Louis Van Tonder (Obiter, 2021)
Important pronouncements of legal principle were recently made by the Competition Appeal Court and Constitutional Court on the determination of predatory pricing under section 8 of the Competition Act 89 of 1998. These pronouncements must now be seen in the context of the subsequent commencement of the Competition Amendment Act 18 of 2018. In light of these developments, this three-part series of articles evaluate the law relating to the economic concept of predatory pricing under the Competition Act. In this context, the crucial elements of dominance and abuse are also discussed. The first in this series of three articles critically evaluated the law on the determination of single-firm dominance under section 7 of the Competition Act. The second article discussed the basic forms of abuse, the meaning of abuse, tests that have been developed to identify exclusionary conduct, the criticism of the traditional theory of predatory pricing, the main strategic economic theories of predatory pricing and non-pricing theories of predation. This article focuses on the law of predatory prices under section 8(1)(c) and 8(1)(d)(iv) of the Competition Act. Pursuant to section 1(3) of the Competition Act, when interpreting or applying the Competition Act, appropriate foreign and international law may be considered. This is complementary to section 1(2)(a), which directs that the Competition Act must be interpreted in a manner that is consistent with the Constitution and which gives effect to the purposes set out in section 2. In light hereof and where appropriate, the South African position is mainly compared with the position in the European Union and the United States.